Description of two new Ancylis Hilbner, [1825], from Russian Far East (Tortricidae Olethreutinae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Two new species of the genus Ancylis Hubner, [1825], (Lepidoptera Tortricidae) are described from Progranitchnyj region and Ussuriysk region of Russian Far East, Ancylis barabashi sp.n. and Ancylis ussuricana sp.n. Ancylis barabashi Trematerra & Li sp.n. is close to Ancylis sculpta Meyrick, 1912, and Ancylis ussuricana Trematerra & Li sp.n. is similar to Ancylis badiana (Denis & Schiffermuller,1775). The new species can be easily separated by a few morphological characters of the male genitalia.
Keywords: Lepidoptera Tortricidae; Ancylis; Russian Far East; new species